Implementation of Ibn Sina's Educational Thoughts in Today's Guidance and Counseling - Robbi Asri; Sufyarma; Yeni Karneli; Rendy Amora (Quality : Journal Of Education, Arabic And Islamic Studies, 2024)
This article discusses the implementation of Ibn Sina's educational thoughts in today's guidance and counseling. Ibn Sina is one of the figures who has made a major contribution to the scientific treasures of Islam, especially those related to Islamic education. Besides that, the educational thoughts of Ibn Sina, or also known as Avicenna, can be implemented in the context of today's guidance and counseling by exploring his relevant philosophical concepts. Ibn Sina, a medieval Islamic philosopher and scholar, emphasized the importance of holistic education involving the physical, intellectual, emotional and spiritual aspects of the individual. In modern guidance and counseling, this concept can be applied by paying attention to the client's needs as a whole, not just focusing on the psychological aspect alone. Apart from that, Ibn Sina's thoughts about self-discovery and developing individual potential can also be the basis for a counseling approach that is oriented towards client growth and empowerment. By combining Ibn Sina's views with contemporary psychological theories, guidance and counseling practitioners can create a more comprehensive and integrated approach to helping clients achieve their holistic well-being. The method used is a literature review with critical analysis of research being conducted on a specific topic.